2014
DOI: 10.4103/0971-4065.132992
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and effector T cells changes in remission and resistant state of childhood nephrotic syndrome

Abstract: Idiopathic minimal change disease is a disorder of T-cell dysfunction. The relative predominance of regulatory T cells (Tregs), Th1, and Th2 cells in nephrotic syndrome (NS) remains controversial. Imbalance in peripheral blood regulatory and effector T cells (Teff) are linked to cell mediated immune response and may be associated with steroid response in NS. Peripheral blood CD4 + CD25 + FoxP3 + (Tregs), CD4 + IFN-γ+ (Th1), and CD4 + IL-4 + (Th2) lymphocytes were analyzed in 22 steroid-sensitive NS (SSNS) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…During remission, Treg cell numbers rose, with a corresponding increase in IL-10 and TGF-β production ex vivo. 96 , 102 - 104 Similar findings were noted in adult MCD patients; the peripheral blood Th17/Treg cell ratio and Th17-related plasma cytokines (IL-17 and IL-23) were increased and Treg cells and Treg-related cytokines (TGF-β1 and IL-10) were decreased during proteinuria and normalized after the induction of remission. 106 Jaiswal et al found lower percentages of Treg cells and Treg/Th1 ratios in glucocorticoid resistant MCD, compared with glucocorticoid responsive MCD in remission and healthy controls.…”
Section: Possible Mechanisms Of Action Of Rtx In MCDsupporting
confidence: 67%
See 1 more Smart Citation
“…During remission, Treg cell numbers rose, with a corresponding increase in IL-10 and TGF-β production ex vivo. 96 , 102 - 104 Similar findings were noted in adult MCD patients; the peripheral blood Th17/Treg cell ratio and Th17-related plasma cytokines (IL-17 and IL-23) were increased and Treg cells and Treg-related cytokines (TGF-β1 and IL-10) were decreased during proteinuria and normalized after the induction of remission. 106 Jaiswal et al found lower percentages of Treg cells and Treg/Th1 ratios in glucocorticoid resistant MCD, compared with glucocorticoid responsive MCD in remission and healthy controls.…”
Section: Possible Mechanisms Of Action Of Rtx In MCDsupporting
confidence: 67%
“…Although data presented by Araya et al suggest that the percentage of Treg cells is similar in healthy controls and pediatric patients with MCD in relapse or in remission, 101 others have reported that the number and percentage of peripheral Treg cells (CD4 + CD25 + Foxp3 + ) were significantly decreased during active MCD, compared with patients in remission and healthy controls. 96 , 102 - 105 In contrast, the peripheral Th1 and Th2 cell abundance was increased during active nephrotic states and decreased during remission, along with the ex vivo expression of interferon (IFN)–γ and IL-4, major cytokines of Th1 and Th2 cells, respectively. During remission, Treg cell numbers rose, with a corresponding increase in IL-10 and TGF-β production ex vivo.…”
Section: Possible Mechanisms Of Action Of Rtx In MCDmentioning
confidence: 99%
“…Many previous studies had documented high serum levels of these 3 cytokines in INS patients, 3 , 4 , 12 17 nevertheless the literature on the level of these cytokines in the urine of INS patients in particular and in patients with kidney disease, in general, is scarce. It is more likely that most cytokines exert their effects in situ at their site of production; therefore, their level in urine is more reflective, than serum levels, of the immune changes taking place during relapse and remission.…”
Section: Discussionmentioning
confidence: 99%
“… 7 9 Nevertheless, recently, a decrease in the number and/or function of T-regulatory cells (Tregs), which are important modulators of the functions of the effector T-cells, was reported to be a prerequisite for the development of INS. 1 , 3 , 10 12 …”
Section: Introductionmentioning
confidence: 99%
“…Another study performed on 21 adults with primary MCD demonstrated decreased suppressive capacity of Foxp3 + Treg cells, although patients had similar numbers of circulating Foxp3 + Treg cells in comparison with controls [ 19 ]. In another report, 21 children with steroid-resistant nephrotic syndrome had increased ratios of circulating interferon- (IFN-) gamma-secreting Th1 cells and IL-4-secreting Th2 cells over Foxp3 + Treg cells when compared to 22 children with steroid-sensitive nephrotic syndrome in clinical remission and 14 healthy controls [ 20 ]. The interplay between Th17 cells and Foxp3 + Treg cells has also been reported in two studies.…”
Section: Introductionmentioning
confidence: 99%